Sanad Surah Al-fātiḥah: Amalan Pengijazahannya Di Malaysia - Mohamad Redha Mohamad; Muhammad Firdaus Abdul Manaf; Muhammad Zaid Shamshul Kamar; Norazman Alias (KUIS, 2024)
VOL. 5 NO. 2 (2022) Page (56-66)